Etika Komunikasi Dalam Tinjauan Al-Qur’an Dan Hadis - Muhammad Aiman Nabiil Syarif; Muh Ilham; Tasbih Tasbih (KAMPUS AKADEMIK PUBLISING, 2026)
Communication research is a fundamental human necessity which, in Islam, is considered an act of worship when conducted in accordance with the guidance of the Qur’an and the Sunnah. However, the contemporary digital era presents complex challenges, such as the widespread dissemination of hoaxes, hate speech, and cyberbullying, indicating a decline in the ethical quality of communication. This article aims to re-explore the foundations of Islamic communication ethics as a response to these phenomena. Employing a thematic approach to Qur’anic verses and Prophetic traditions (Hadith), the study finds that Islam offers a comprehensive framework for communication through the concept of the six Qaulan principles (truthful, gentle, noble, good, effective, and pleasant speech), as well as ethical principles derived from Hadith, including self-restraint, honesty, conflict avoidance, and informational productivity. The discussion affirms that, in Islam, communication is not merely an exchange of messages, but a form of moral accountability before Allah swt, which must be grounded in the values of tawhid and humanity.